2001
DOI: 10.1136/ip.7.2.155
|View full text |Cite
|
Sign up to set email alerts
|

A geographic analysis of motor vehicle collisions with child pedestrians in Long Beach, California: comparing intersection and midblock incident locations

Abstract: Objectives-The purpose of this study was to use geographic information system (GIS) software to locate areas of high risk for child pedestrian-motor vehicle collisions in the city of Long Beach and to compare risk factors between midblock and intersection collisions. Methods-Children 0-14 years of age involved in a motor vehicle versus pedestrian collision that occurred on public roadways in Long Beach, CA, between 1 January 1992 and 30 June 1995, were identified retrospectively from police reports. The GIS so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 18 publications
7
38
0
2
Order By: Relevance
“…The majority of collision involving pedestrian age 17 and younger and 65 and older occurred near home. There is extensive pediatric literature addressing the proximity of child auto-pedestrian collisions to victims' homes or schools [Agran et al, 1994;Malek et al, 1990;Braddock et al, 1994;Roberts et al, 1997;Lightstone et al, 2001;La Scala et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of collision involving pedestrian age 17 and younger and 65 and older occurred near home. There is extensive pediatric literature addressing the proximity of child auto-pedestrian collisions to victims' homes or schools [Agran et al, 1994;Malek et al, 1990;Braddock et al, 1994;Roberts et al, 1997;Lightstone et al, 2001;La Scala et al, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Literature exploring child pedestrian injury suggests that collisions often occur close to children's homes or schools [Agran, Winn, Anderson, 1994;Malek, Guyer, Lescoheir, 1990;Braddock, Lapidus, Cromley, 1994;Roberts et al, 1997;Lightstone, Dhillon, Peek-Asa, 2001;La Scala, Guenewald, Johnson, 2004]. Additionally, past studies have identified factors associated with the risk of adult pedestrian collision and injury such as age and gender [La Scala, Gerber, Gruenewald, 2000;Graham, Glaister, Anderson, 2005;Hijar, Kraus, Tovar, 2001;Gorrie, Brown, Waite, 2008], alcohol involvement [La Scala et al, 2000;Shuurman, Cinnamon, Crooks, 2009;Paulozzi, 2006], and socio-economic status [Rivara and Barber, 1985;La Scala et al, 2000;Graham et al, 2005;Chakravarthy, Anderson, Ludlow, 2010] among others.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 15 years, child injury surveillance research has increasingly included explicit use of GIS for cross-sectional studies mapping locations of injuries and providing spatial analysis of their environmental and social correlates. [53][54][55][56][57][58][59] However, within these types of studies, the spatial unit of analysis has commonly been the census tract, zip code tabulation area, or other relatively large and diverse area both in terms of physical infrastructure and in demographic characteristics. Furthermore, despite the substantive and methodological contributions of these studies, a need remains for expansion into longitudinal investigations of these behaviors and relationships, as well as those focused on evaluation of specific interventions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ces deux caractéristiques sont ainsi considérées comme des facteurs de risque indirects. La dimension socio-économique inclut quant à elle deux composantes : la défavorisation des ménages et la densité populationnelle, toutes deux reconnues maintes fois comme des facteurs de risque importants en accidentologie (Dougherty et al 1990 ;Braddock et al 1991 ;Kendrick 1993 ;Agran et al 1996 ;Roberts et al 1996 ;Laflamme et Diderichsen 2000 ;Wazana et al 2000 ;Lightstone et al 2001 ;LaScala et al 2004 ;Adams et al 2005 ;Graham et al 2005 ;Sonkin et al 2006). Finalement, la dimension scolaire prend en considération les politiques de transport scolaire sous l'hypothèse qu'elles ont une influence sur le mode de transport vers l'école, celui-ci affectant encore une fois l'exposition au trafic.…”
Section: Cadre Conceptuelunclassified